Effect of market-driven strategies on the competitive growth of SMEs in Lesotho - Donald O. E. Amadasun; Ashley T. Mutezo (Journal of Innovation and Entrepreneurship, 2022)
This paper established some market-driven strategies that influence the competitive growth of small and medium-sized enterprises in Lesotho. The paper identified the following factors; market orientation, competitive intensity, and technological dynamics as variables that influence SMEs' competitive growth. The investigation shows that these critical factors of market-driven strategies are significant market facets in the enterprise that could capacitate SME entrepreneurs and managers to attain competitive growth.~The results indicated that the factors used to measure market-driven strategies influence SMEs competitive growth. More specifically, the independent variables of market orientation, competitive intensity and technological dynamics are seen as key tenets of market-driven strategies that influence small and medium-sized enterprises' competitive growth.~From the analyses, this paper recommended that market-driven strategic constructs of market orientation, competitive intensity and technological dynamics are inimitable and tangible significant resources if harnessed in the enterprises, could serve as critical operational factors that influence SMEs competitive growth in Lesotho.
Keywords: 650; Competitive growth; Competitive intensity; Market orientation; Market-driven strategies; Small and medium-sized enterprises; Technological dynamics